2005
DOI: 10.1124/jpet.104.080481
|View full text |Cite
|
Sign up to set email alerts
|

Group III Metabotropic Glutamate-Receptor-Mediated Modulation of Excitatory Transmission in Rodent Substantia Nigra Pars Compacta Dopamine Neurons

Abstract: Glutamate plays an important role in the regulation of dopamine neuron activity. In particular, the glutamatergic input from the subthalamic nucleus is thought to provide control over dopamine neuron firing patterns. The degeneration of dopamine neurons in the substantia nigra pars compacta (SNc) observed in Parkinson's disease (PD) is believed to be due to a complex interplay of factors, including oxidative stress and mitochondrial dysfunction. Although glutamate is not the primary cause of cell death in PD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
102
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 38 publications
(49 reference statements)
3
102
0
Order By: Relevance
“…To further test the hypothesis that mGluR8 is responsible for L-AP4-induced regulation of synaptic transmission at the SC-CA1 synapse in neonatal animals, we determined the effect of PHCCC (30µM) on the response to a concentration of L-AP4 that induces a clear but relatively small response. This concentration of PHCCC was chosen based on our previous findings that this concentration potentiates mGluR4-mediated responses at other synapses in brain slice preparations Valenti et al, 2005). Consistent with predominant roles of mGluR8 and mGluR7 in neonatal and adult animals, PHCCC had no effect on the responses to submaximal concentrations of L-AP4 in slices from either age group (Fig.…”
Section: Phccc Does Not Potentiate the L-ap4 Effect In Neonatal Or Yomentioning
confidence: 97%
See 1 more Smart Citation
“…To further test the hypothesis that mGluR8 is responsible for L-AP4-induced regulation of synaptic transmission at the SC-CA1 synapse in neonatal animals, we determined the effect of PHCCC (30µM) on the response to a concentration of L-AP4 that induces a clear but relatively small response. This concentration of PHCCC was chosen based on our previous findings that this concentration potentiates mGluR4-mediated responses at other synapses in brain slice preparations Valenti et al, 2005). Consistent with predominant roles of mGluR8 and mGluR7 in neonatal and adult animals, PHCCC had no effect on the responses to submaximal concentrations of L-AP4 in slices from either age group (Fig.…”
Section: Phccc Does Not Potentiate the L-ap4 Effect In Neonatal Or Yomentioning
confidence: 97%
“…As with other allosteric potentiators, PHCCC has no effect on mGluR4 when added alone but dramatically increases the potency of L-AP4 at activating this receptor. Furthermore, PHCCC enhances the effect of L-AP4 at synapses in the globus pallidus and substantia nigra (Valenti et al, 2005) where mGluR4 is the predominant mGluR subtype involved in regulating synaptic transmission. To further test the hypothesis that mGluR8 is responsible for L-AP4-induced regulation of synaptic transmission at the SC-CA1 synapse in neonatal animals, we determined the effect of PHCCC (30µM) on the response to a concentration of L-AP4 that induces a clear but relatively small response.…”
Section: Phccc Does Not Potentiate the L-ap4 Effect In Neonatal Or Yomentioning
confidence: 99%
“…It is likely that the drug reduces the excitatory drive to the pars compacta of substantia nigra, thus limiting the excitotoxic component of MPTP toxicity (Turski et al, 1991;Srivastava et al, 1993;Lange and Riederer, 1994;Sonsalla et al, 1998). This may originate from (1) a reduced release of GABA in the external globus pallidus leading to inhibition of subthalamic glutamatergic neurons projecting to the pars compacta of substantia nigra Matsui and Kita, 2003;Valenti et al, 2003), or (2) a reduced glutamate release in the pars compacta of substantia nigra mediated by presynaptic mGlu4 receptors (Valenti et al, 2005). Infusion of PHCCC into the external globus pallidus protected the ipsilateral nigrostriatal pathway against MPTP toxicity to an extent similar to that found after systemic injection of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lack of mGlu4 receptors in knock-out mice might be compensated by adaptive changes involving other group III mGlu receptor subtypes. Interestingly, Valenti et al (2005) found that both mGlu4 and mGlu8 receptors modulate excitatory transmission in mouse substantia nigra pars compacta dopamine neurons and that responses to the mGlu8 receptor agonist ( S)-3,4-dicarboxyphenylglycine are amplified in mGlu4…”
Section: Discussionmentioning
confidence: 99%
“…This activation has been considered as a promising therapeutic approach for the treatment of Parkinson's disease, anxiety, schizophrenia, depression, chronic pain, epilepsy and addiction [2].Three group III mGluR subtypes (mGluRs 4, 7, and 8) are expressed in the basal ganglia, a group of brain nuclei that are involved in the control of motor function and are critical to the motor deficits observed in Parkinson's disease (PD). It is interesting that activation of mGluR4 reduces transmission at a key basal ganglia synapse (striatopallidal synapse) that is believed to be overactive in patients with PD, and this effect is lost in mGluR4 knockout animals [3]. Due to the lack of selectivity of orthosteric ligands for the mGluRs, much effort has now been directed at identifying and examining the utility of compounds that act via allosteric sites on the receptor.…”
Section: Introductionmentioning
confidence: 99%